Behaviors and actions of the strength and conditioning coach in fostering a positive coach-athlete relationship - Carson, F.; Blakey, M.; Foulds, S. J.; Hinck, K.; Hoffmann, S. M. (The Journal of Strength and Conditioning Research, 2022)
A number of models have been developed to explain the various factors that affect coach-athlete interactions; however, they have had limited application to strength and conditioning (S&C). A systematic review of the literature was completed using the databases SPORTDiscus Full Text, MEDLINE, Global Health, Academic Search Complete, and PsychINFO, sourcing articles related to S&C coach-athlete relationships. An initial search yielded 1,364 articles, which when screened against the inclusion criteria was narrowed to 8 articles relating specifically to the S&C coach-athlete relationship. Four major themes were identified throughout the included articles: leadership styles; perceptions of leadership; coach knowledge, experience, and training; and building relationships. These themes highlighted that positive coach-athlete interactions are fostered through a mutual understanding of the S&C coach's responsibility to improve performance and reduce injury through scientific methods, with an awareness of different psychosocial behaviors of both the coach and the athlete. This will create a mutual interconnectedness whereby both parties can participate in a functional dyad. Three practical applications deduced from the findings identified the importance of building an autonomy-supportive environment, keeping knowledge and expertise at a high standard, and embracing the whole person rather than just the athlete. These teachings aim to guide S&C coaches through the necessary actions and behaviors recommended to successfully build and foster positive S&C coach-athlete relationships.